SPIRITUAL WELL-BEING OF PATIENTS WITH CANCER OF GYNAECOLOGI - Sellyan Septiani Berly; Efri Widianti; Ermiati E (Journal of Maternity Care and Reproductive Health, 2018)
Gynaecological cancer is a women’s disease with a high incidence. Problems that occur in gynaecological cancer patients include physical, psychosocial, and spiritual aspects. However, spiritual well-being in gynaecological cancer patients is ignored so that it is not clearly seen how the condition of patients’ spiritual well-being. This study aimed to describe the spiritual well-being of gynaecological cancer patients in a referral hospital in Bandung. The design of this study used quantitative descriptive with a total sample method. The number of samples was 41 patients. The study was conducted for one month from June to July, the sampling technique used was accidental sampling. The instrument in this study used the Spiritual Index of Well-being (SIWB). Data were analysed using frequency distributions, averages, and percentages. The results showed that 68.29% of respondents had a high level of spiritual well-being, and 21.79% had a low level of spiritual well-being. The self-efficacy sub-variable had an average value of 19.46 lower than the life-scheme sub-variable of 22.29. The item that has the highest value is "In this world, I don't know where I feel comfortable" and the item that has the lowest value is "There's not much I can do to help myself". The conclusion of the results of this study is that most respondents have a high level of spiritual well-being. Self-efficacy is a sub-variable with the lowest average value.Keywords: gynaecological cancer, life-scheme, self-efficacy, spiritual